The Role of the Tamsulosin in the Medical Expulsion Therapy for Distal Ureteral Stones - Taimoor Jan; Haris Jameel; Mehnaz Jabeen; Rabeea Saleem; Maheshwari , Pardeep Kumar; Murli Lal (International Journal of Endorsing Health Science Research, 2022)
Background: This study aims to assess Tamsulosin's contribution to spontaneous medical expulsion for distal ureteral stones. Methodology: The research included 113 patients diagnosed with the distal ureteral stone of 4-10 mm. These patients were introduced to 0.4 mg of Tamsulosin. The technique of KUB ultrasonography was adopted as the means of assessment of stone status following the period of Tamsulosin introduction. Results: There was a high frequency of Spontaneous expulsion among the enrolled patients (86.73%). Furthermore, there was a significant effect of age on the frequency of spontaneous expulsion (p=0.008). While gender, disease duration, stone size, and side had no significant effect on the frequency of spontaneous expulsion after Tamsulosin administration for distal ureteral stones. Conclusion: It is concluded that Tamsulosin has an efficient impact on triggering spontaneous expulsion among patients with distal ureteral stones.